English skills with readings - Langan, John (McGraw - Hill, 2006)
By focusing on a wide range of reading and study skills required in the academic world, English Skills with Reading gives instructors the flexibility to address student needs that might otherwise require several texts. . The highly versatile organization divides topics into focused, self-contained modules that can be covered in any order with the result that the text can be adapted to fit any teaching or learning situation.